Social-psychological support system for people who have experienced the consequences of war trauma - Ломакін, Геннадій (Psychosomatic Medicine and General Practice, 2024)
The relevance of this article is driven by the social situation that has emerged in Ukrainian society amidst Russian aggression and full-scale war, necessitating the resolution of pressing issues faced by the most vulnerable segments of the population. This paper analyzes and examines modern approaches and peculiarities of implementing the social-psychological support system for war-affected vulnerable populations in Ukraine, as well as providing assistance to combatants of the Armed Forces of Ukraine. The main directions of social-psychological work with this category of citizens are outlined with the aim of overcoming the negative impacts of war. Examples of successful implementation of the social-psychological support system by the public organization "Kharkiv City Association of Afghanistan Veterans (Internationalist Warriors)" are provided, utilizing methods such as engaging veterans in social activities and «helping for self-help» with a focus on the post-traumatic growth of the affected individuals.